2018
DOI: 10.1002/macp.201800211
|View full text |Cite
|
Sign up to set email alerts
|

Silver Nanoparticles Engineered Polystyrene‐Poly(N‐isopropylmethacrylamide‐acrylic acid) Core Shell Hybrid Polymer Microgels for Catalytic Reduction of Congo Red

Abstract: Polystyrene‐poly(N‐isopropylmethacrylamide‐acrylic acid) [pSty‐p(NIpmam‐AC)] core shell microgels loaded with silver nanoparticles (NPs) as a recyclable catalyst for rapid reduction of Congo Red (CR) dye in aqueous medium is reported for the first time. Catalytic activity of Ag‐pSty‐p(NIpmam‐AC) core shell composite microgels is measured by adopting the reduction of CR as a benchmark reaction. Restriction of Ag NPs in single layered p(NIpmam‐AC) shell of Ag‐pSty‐p(NIpmam‐AC) core shell composite microgels enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(27 citation statements)
references
References 49 publications
0
27
0
Order By: Relevance
“…Begum et al reported that immobilization of Nobel NPs to various supports (graphine oxide, porous silica, and alumina) have encountered the following disadvantages such as preparation methods required long time and nucleation sites of inorganic sheets suffers oxidation. Thus, to overcome this, they prepared microgel fabricated noble NPs to use in several chemical reaction . Ghosh et al observed that NPs doped or supported with another metal boosted the catalytic efficiency to great extent due to synergistic effect .…”
Section: Introductionmentioning
confidence: 99%
“…Begum et al reported that immobilization of Nobel NPs to various supports (graphine oxide, porous silica, and alumina) have encountered the following disadvantages such as preparation methods required long time and nucleation sites of inorganic sheets suffers oxidation. Thus, to overcome this, they prepared microgel fabricated noble NPs to use in several chemical reaction . Ghosh et al observed that NPs doped or supported with another metal boosted the catalytic efficiency to great extent due to synergistic effect .…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it would be desirable to have an efficient procedure to decompose this dye. The work by Naseem et al reveals an enhanced reduction efficiency of Congo Red by this particular core-shell microgel dispersion type [104].…”
Section: Applications Of Core-shell Microgels In Catalysismentioning
confidence: 90%
“…[354][355][356] Many studies have examined hydrogels with core-shell structures. For example, Farooqi et al [357] synthesized polystyrene-poly (N-isopropylmethacrylamide-acrylic acid) core-shell microgels loaded with silver nanoparticles (NPs), which were used as a recyclable catalyst for the rapid reduction of Congo Red dye. The same research group [358] also used a precipitation polymerization method to fabricate nearly mono-dispersed spherical core-shell polymer microgels consisting of an un-responsive polystyrene (PSt) core and a temperature-and pH-responsive poly(N-isopropylmethacrylamide-acrylic acid).…”
Section: Nanogelsmentioning
confidence: 99%